2020
DOI: 10.1177/0961203320959716
|View full text |Cite
|
Sign up to set email alerts
|

A comparison and review of three sets of classification criteria for systemic lupus erythematosus for distinguishing systemic lupus erythematosus from pure mucocutaneous manifestations in the lupus disease spectrum

Abstract: Although the original purpose of the systemic lupus erythematosus (SLE) classification criteria was to distinguish SLE from other mimic diseases, and to facilitate sample selection in scientific research, they have become widely used as diagnostic criteria in clinical situations. It is not known yet if regarding classification criteria as diagnostic criteria, what problems might be encountered? This is the first study comparing the three sets of classification criteria for SLE, the 1997 American College of Rhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…A total of nine original studies were included in our systematic review, including five retrospective cohort studies (including six pairs of study cohorts) (6,7,9,10,14) and four case-control studies (11)(12)(13)25); of them, three studies were conducted under the circumstances that the clinical diagnosis was prior to classification criteria scoring, causing a high risk of bias (10,12,14). The scoring of EULAR/ACR-2019 in derivative cohort by Aringer et al was obtained by rheumatologists without knowing its specific classification threshold, thus its bias risk is rated as "high" (6).…”
Section: Methodological Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…A total of nine original studies were included in our systematic review, including five retrospective cohort studies (including six pairs of study cohorts) (6,7,9,10,14) and four case-control studies (11)(12)(13)25); of them, three studies were conducted under the circumstances that the clinical diagnosis was prior to classification criteria scoring, causing a high risk of bias (10,12,14). The scoring of EULAR/ACR-2019 in derivative cohort by Aringer et al was obtained by rheumatologists without knowing its specific classification threshold, thus its bias risk is rated as "high" (6).…”
Section: Methodological Qualitymentioning
confidence: 99%
“…In a Chinese study by Teng et al, there were 9 patients only satisfying EULAR/ACR-2019, of which 4 were attributed to fever item; one with oral ulcers, leucopenia, hemolytic anemia, thrombocytopenia and antinuclear antibody can just be classified by SLICC-2012; on the contrary, another one with acute cutaneous lupus, photosensitivity, anti-dsDNA, ANA met ACR-1997 and EULAR/ACR-2019 but not SLICC-2012; notably, a total of 33 patients satisfying both EULAR/ACR-2019 and SLICC-2012 lost SLE classification using ACR-1997 (11). Jin et al pointed out 132 SLE patients with missed diagnosis by ACR-1997, with a high prevalence of renal disorder, non-scarring alopecia and hypocompletemia; no photosensitivity in SLICC-2012 was accountable for 8 SLE patients who lost SLE classification by SLICC-2012; there were 29 SLE patients not classified by EULAR/ACR-2019, of whom the proportion was higher in negative ANA, mucocutaneous lesions, joint involvement, renal disorder and hematological diseases (25).…”
Section: Characteristics Of Patients Not Meeting the Three Classifica...mentioning
confidence: 99%
“…Lee et al 17 showed similar specificity of all three SLE criteria in their Korean patients. Jin et al 21 studied 2097 Chinese patients with SLE and isolated cutaneous lupus. The sensitivity of the EULAR/ACR criteria for SLE was 96.8%, which was similar to the SLICC criteria (98.3%).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies that analyzed the performances of these three classification criteria in different populations have yielded various results. 1,2,8,11,14,[16][17][18][19][20][21][22][23][24][25][26] The sensitivities and specificities varied considerably in these studies. Sensitivities as low as 56% 21 and as high as 100% 14,21,25 and specificities as low as 56.5% 20 and as high as 100% 21,23 have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…1,2,8,11,14,[16][17][18][19][20][21][22][23][24][25][26] The sensitivities and specificities varied considerably in these studies. Sensitivities as low as 56% 21 and as high as 100% 14,21,25 and specificities as low as 56.5% 20 and as high as 100% 21,23 have been reported. One possible reason for this variation is the different patient subgroups and different populations in which the studies were conducted.…”
Section: Discussionmentioning
confidence: 99%